2020
DOI: 10.1038/s41598-020-80444-5
|View full text |Cite
|
Sign up to set email alerts
|

A glimpse of antimicrobial resistance gene diversity in kefir and yoghurt

Abstract: Antimicrobial resistance (AMR) is a global threat gaining more and more practical significance every year. The main determinants of AMR are the antimicrobial resistance genes (ARGs). Since bacteria can share genetic components via horizontal gene transfer, even non-pathogenic bacteria may provide ARG to any pathogens which they become physically close to (e.g. in the human gut). In addition, fermented food naturally contains bacteria in high amounts. In this study, we examined the diversity of ARG content in v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 55 publications
2
44
0
Order By: Relevance
“…We found numerous and diverse ARGs in commonly used bacterial strains of kefir and yoghurt products. Thus, the results of our study support the findings of several other recent studies which have also identified ARGs in probiotics 5,6,[33][34][35] . We also found that many of them have the potential to be mobile.…”
Section: /13supporting
confidence: 92%
See 1 more Smart Citation
“…We found numerous and diverse ARGs in commonly used bacterial strains of kefir and yoghurt products. Thus, the results of our study support the findings of several other recent studies which have also identified ARGs in probiotics 5,6,[33][34][35] . We also found that many of them have the potential to be mobile.…”
Section: /13supporting
confidence: 92%
“…The transfer of antimicrobial resistance genes (ARGs) is enhanced by being linked with mobile genetic elements (MGEs), particularly plasmids 3,4 . In this study, as a continuation of our work 5,6 , we explored the possible development of AMR due to HGT during the fermentation of food produce derived from animal sources, namely kefir and yoghurt products. The multiplication of bacteria during the fermentation process is widely known and understood.…”
Section: Introductionmentioning
confidence: 99%
“…In the Bifidobacterium genus, ARGs were associated with four species ( B. animalis , B. bifidum , B. breve and B. longum ). None of the B. animalis , B. bifidum , B. breve and B. longum related B. adolescentis rpoB mutants conferring resistance to rifampicin and tet(W/N/W) are specific for the identified species but both genes have previously been described in them [ 6 , 52 , 53 , 54 , 55 ]. B. bifidum ileS conferring resistance to mupirocin reported in B. bifidum supposedly cannot be exclusively linked to this species of the genus, but it had been identified in it before [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the challenge is to monitor and select the starting culture strains of fermented foods in order to decrease the intake of ARGs via foods. (24)…”
Section: Safety Considerationsmentioning
confidence: 99%